A theory and outcome evaluation of the Allan Gray Orbis Foundation (AGOF) Association Programme - Ndamase, Nozuko (Accounting and Accountability in Africa, 2026)
This dissertation presents a comprehensive evaluation of the Association Programme of the Allan Gray Orbis Foundation (AGOF), which is designed to foster entrepreneurial activities among its participants. The evaluation employs a dual focus, integrating both theory evaluation and outcome evaluation methodologies to assess the effectiveness of the programme. The theory evaluation utilizes a descriptive research design, examining the programme's Theory of Change (ToC) and aligning it with empirical evidence. Key methodologies included an extensive literature review and semi-structured interviews conducted with subject matter experts. Data analysis was performed using thematic analysis to ensure a robust understanding of the programme's underlying assumptions and causal pathways. The outcome evaluation, adapted the Success Case Method (SCM), focuses on identifying and analysing successful and non-successful cases among programme participants. Initially, a review using existing AGOF database was conducted to identify potential success cases, followed by in-depth interviews to gather qualitative data from selected individuals. Findings from the theory evaluation indicate that the AGOF Association Programme's ToC is supported by empirical evidence, emphasising the criticality of mentorship and resource accessibility for entrepreneurial success. The outcome evaluation reveals that many fellows successfully established socially responsible, high-impact enterprises while also highlighting challenges regarding access to financial resources and the application process for funding. Overall, the integrated findings from both evaluations reflect the programme's positive impact on fostering entrepreneurial capabilities among participants while also pointing out areas for improvement, particularly in enhancing funding accessibility and ongoing support mechanisms for fellows.